PARTICIPAÇÃO DA POPULAÇÃO INDÍGENA SUL-MATO-GROSSENSE NOS DIREITOS POLÍTICOS PASSIVOS - Almeida Pereira, Guilherme; Knapp, Cássio (Suffragium - Scientific Journal of the Regional Electoral Court of Ceará (TRE-CE), 2025)
ABSTRACT: In Brazil, there is an increase in the number of people who declare themselvesindigenous, with Mato Grosso do Sul being the third state with the largest share of thispopulation. In this context, this article aims to identify the reality of the participation of theindigenous population of Mato Grosso do Sul in the exercise of passive political rights,consistent with the citizen's ability to be elected and exercise an elective mandate. Usingbibliography, data from IBGE, the Superior Court and collected in interviews andquestionnaires, it examines the concept of indigenous people; provides a national and localoverview of this population; discusses the concept and types of political rights; addresses thephenomenon of political representation; and analyzes the reality and vision of electedindigenous people on the subject. With the research it was possible to observe that there is noeffective indigenous participation in passive political rights, motivated mainly by economic andcultural issues and lack of identity of political parties in defense of the indigenous cause.Keywords: Passive political rights, indigenous participation, reality in Mato Grosso do Sul.